Electrothermal model of monolithic TOPSwitch regulators. (12th April 2013) - Górecki, Krzysztof
ABSTRACT: In the paper, an electrothermal compact model of monolithic switching‐mode voltage regulators belonging to the TOPSwitch family is proposed. The description of this model and some results of the experimental verification of its correctness on the example of the regulator TOP222Y are presented. The proposed model can be used to calculate the terminal voltages and currents of the investigated device and the internal temperature of this regulator, too. The satisfying agreement between the calculated and measured characteristics of the switching‐mode power supply including the considered integrated circuit was reached. Copyright © 2013 John Wiley & Sons, Ltd.